Deceived - Alhunaiyyan, Abdullah; Cabanas, Adriana; Al-Awaji, Turki; Alsulami, Anwar; Almutari, Abdullah; Peterson, Will (My University, 2016)
Cast: Hazem Kotami, Lulwa Al-Qaoud, Ricardo Gimenez, Denise Bernie, Adriana Cabanas. Special Thanks: Anwar Alsulami, Abdullah Almutari, Will Peterson.
Citation: AH PRO Group. (2016). Deceived. K-State 48 Film Festival, 2016
Keywords: AH PRO Group; K-State 48 Film Festival